Gracz w roli narratora – na przykładzie gier komputerowychtypu FPP - Konczalski, Konczalski (Załącznik Kulturoznawczy, 2014)
Even though film is having the biggest esthetical impact on videogames, player’s participation during the gameplay suggests rather a theatrical – performative trope. It shouldn’t be however the reason to question narrative aspects of videogames. In this article I signal that mainstream videogames are drifting away from competition and moving closer to narration of interesting stories, in which a player is participating and also becomes a narrator. I describe this occurrence using Erika Ficher-Lichte’s performative esthetics and Jean Baudrillard’s simulation theory.